PERILAKU PROSOSIAL SISWA REGULAR DI SEKOLAH INKLUSIF: BAGAIMANA PERAN PERSEPSI IKLIM SEKOLAH? - Dea Manolini Putri; Isrida Yul Arifiana; Suroso (PSYCHOPEDIA : Jurnal Psikologi Universitas Buana Perjuangan Karawang, 2023)
This research was conducted to determine the relationship between perceptions of school climate and the prosocial behavior of regular students in inclusive schools. The research will be conducted on a subject of 209 regular students at SMP X Kota Surabaya, and data collection will be carried out online. The measuring instrument used in this study uses a school climate perception scale and a prosocial behavior scale with the Likert scale model. The data obtained were analyzed using Spearman's rho correlation analysis technique. The results of the study state that there is a positive and very significant relationship between prosocial behavior and perceptions of school climate, which means that the more positive a perception of school climate is, the higher the prosocial behavior of regular students in inclusive schools. Keywords: Perceptions of school climate, prosocial behavior, inclusive schools Penelitian ini dilakukan guna mengetahui hubungan antara persepsi iklim sekolah dan perilaku prososial siswa reguler di sekolah inklusif. Penelitian akan dilakukan pada partisipan subjek sebanyak 209 siswa regular di SMP X Kota Surabaya dan pengambilan data dilakukan secara online. Alat ukur yang digunakan dalam penelitian ini menggunakan skala persepsi iklim sekolah dan skala perilaku prososial dengan model skala likert. Data yang diperoleh di analisis menggunakan teknik analisa korelasi Spearman’s rho. Hasil penelitian menyebutkan bahwa terdapat hubungan positif dan sangat signifikan antara perilaku prososial dan persepsi iklim sekolah, yang artinya bahwa semakin positif suatu persepsi iklim sekolah maka perilaku prososial yang dimiliki siswa reguler di sekolah inklusif akan semakin tinggi. Kata Kunci: Persepsi iklim sekolah, perilaku prososial, sekolah inklusif